HERBISIDA ORGANIK (RACUN RUMPUT) YANG RAMAH LINGKUNGAN DAN HASIL BUDI DAYA AMAN DIKONSUMSI DI DESA WINONG KECAMATAN MANCAK KABUPATEN SERANG - Ahmad Mukhlis; Aprilia Virahayu; Mohammad Saifussuja Alfaqih (Indonesian Collaboration Journal of Community Services, 2021)
Winong Village with the motto “Desa Siaga” is one of the villages with a journey of about 4 km from the Mancak sub-district office in Serang Regency, Banten Province. The problems faced by Winong Village are the lack of resources and the community's economy. This happens because the land use is not optimal. Agricultural, plantation and craft activities also tend to be less dominant in generating increased income. One of the efforts for land management is to utilize abundant natural resources, namely coconut water which is added with other organic ingredients so that organic herbicides (grass poisons) can be made which are environmentally friendly and the cultivation results are safe for consumption.